2021
DOI: 10.1007/s00432-021-03710-7
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in the landscape of cancer

Abstract: Introduction Cannabinoids are a group of terpenophenolic compounds derived from the Cannabis sativa L. plant. There is a growing body of evidence from cell culture and animal studies in support of cannabinoids possessing anticancer properties. Method A database search of peer reviewed articles published in English as full texts between January 1970 and April 2021 in Google Scholar, MEDLINE, PubMed and Web of Science was undertaken. References of relevant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 155 publications
1
53
1
Order By: Relevance
“…Regarding cannabidiol, it is known to act as a multitarget agent, being an inverse agonist of CB2 receptor, and an antagonist of the non-cannabinoid GPR55 receptor, the transient receptor potential cation channel subfamily M member 8 (TRPM8), and the T-type Ca 2+ channels; moreover, it has been shown to inhibit the fatty acid amide hydrolase (FAAH), responsible for the degradation of anandamide, and the fatty acid-binding protein (FABP), which favors the uptake of anandamide into cell, making it available for intracellular targets, such FAAH or nuclear PPARγ [35,42]. These mechanisms lead to an increased extracellular anandamide concentration, which can indirectly activate CB1 and CB2 receptors [35,42].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cannabidiol, it is known to act as a multitarget agent, being an inverse agonist of CB2 receptor, and an antagonist of the non-cannabinoid GPR55 receptor, the transient receptor potential cation channel subfamily M member 8 (TRPM8), and the T-type Ca 2+ channels; moreover, it has been shown to inhibit the fatty acid amide hydrolase (FAAH), responsible for the degradation of anandamide, and the fatty acid-binding protein (FABP), which favors the uptake of anandamide into cell, making it available for intracellular targets, such FAAH or nuclear PPARγ [35,42]. These mechanisms lead to an increased extracellular anandamide concentration, which can indirectly activate CB1 and CB2 receptors [35,42].…”
Section: Discussionmentioning
confidence: 99%
“…The length of the alkyl side chain may affect the affinity for some biological targets as it has been demonstrated for THC, which is a CBD isomer [ 22 ]. Furthermore, due to their implication in the control of cell growth and death, cannabinoids have been proposed as a new adjuvant in cancer therapy of various malignancies, such as prostate and breast cancer [ 17 , 28 ]. As already described, phytocannabinoids may act via dependent and/or independent cannabinoid receptor mechanisms [ 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase led to the reduction of the mitochondrial transmembrane potential, the opening of the mitochondrial permeability transition pore (mPTP) with subsequent release of cytochrome C into the cytoplasm [ 33 , 34 ], finally resulting in the activation of the mitochondrial-dependent apoptosis pathway. The apoptotic event is preceded by the cell cycle arrest in various cancer models [ 1 , 17 , 35 ]. Another recent study confirmed that the CBD treatment triggered multiple intracellular effects in MCF-7 cells, such as increased Ca 2+ levels, ROS accumulation and ER stress, finally leading to the induction of apoptosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations